Economic Order Quantity (EOQ) Application to Raw Material Inventory Control for SME's - Jahroni; Moh Muksin (Community Service Journal (CSJ), 2023)
The application of the Economic Order Quantity (EOQ) method in managing raw material supplies for Pempek Isti, a micro, small, and medium enterprise (MSME) specializing in Palembang's culinary specialty, Pempek. The study reveals that the current raw material supply management is inefficient, leading to frequent shortages or excess orders, resulting in additional costs and inefficiencies. To tackle this issue, the study proposes the implementation of the EOQ analysis to minimize inventory costs and maximize profits. The research focuses on determining the optimal order quantities for three key raw materials: ikan tenggiri, sago flour, and eggs. After conducting the EOQ analysis, the study identifies the optimal order quantities as 37kg for mackerel fish, 44kg for sago flour, and 7kg for eggs. Furthermore, the study calculates the reorder points for each raw material based on the EOQ method, resulting in 8.36kg for mackerel fish, 8.19kg for sago flour, and 3.23kg for eggs. By implementing the EOQ method, Pempek Isti MSME can accurately estimate the required quantities of raw materials for Pempek production throughout the year. The calculations consider safety stock and lead time, enabling the determination of reorder points and maximum order quantities for each raw material. This information serves as a valuable reference for effectively managing the MSME's raw material supply chain. Overall, the application of the EOQ method is crucial in ensuring an efficient supply chain for Pempek Isti MSME. By implementing proper planning, control, and supervision of raw materials, the company can minimize costs, prevent stockouts, and avoid excessive inventory. This study provides valuable insights into optimizing inventory management, particularly in the context of MSMEs operating in the culinary industry.